Alterations in local activity and functional connectivity in patients with postherpetic neuralgia after short-term spinal cord stimulation - Fan, Xiaochong; Ren, Huan; Bu, Chunxiao; Lu, Zhongyuan; Wei, Yarui; Xu, Fuxing; Fu, Lijun; Ma, Letian; Kong, Cunlong; Wang, Tao; Zhang, Yong; Liu, Qingying; et al. (Frontiers in Molecular Neuroscience, 2022)
Introduction The efficacy of short-term spinal cord stimulation (stSCS) as a treatment for neuropathic pain in patients with postherpetic neuralgia (PHN) has already been validated. However, the potential alterations in brain functionality that are induced by such treatment have yet to be completely elucidated. Methods This study use resting-state functional magnetic resonance imaging (rs-fMRI) to detect the changes in regional homogeneity (ReHo) and degree centrality (DC) related to stimulator-induced pain relief in patients with PHN. A total of 10 patients with PHN underwent an MRI protocol at baseline and after stSCS. Alterations in ReHo and DC were then compared between baseline and after stSCS. We investigated the relationship between clinical parameters and functional changes in the brain. Results Clinical parameters on pain, emotion, and sleep quality were correlated with ReHo and DC. ReHo and DC were significantly altered in the middle temporal gyrus, precuneus, superior frontal gyrus, supramarginal gyrus, inferior parietal lobule, rolandic operculum, middle occipital gyrus, superior parietal gyrus, and the precentral gyrus after stSCS. A significant correlation was detected between ReHo changes in the middle occipital gyrus, precuneus, inferior parietal gyrus, and changes in pain, emotion, and sleep quality. A significant negative correlation was detected between DC changes in the middle temporal gyrus, rolandic operculum, supramarginal gyrus, precuneus, inferior parietal gyrus, and changes in pain, emotion, and sleep quality. Conclusion This study found that stSCS is able to induce ReHo and DC changes in patients with PHN, thus suggesting that stSCS can change brain function to alleviate pain, sleep, and emotional disorder.